BIMBINGAN TEKNIS PENYUSUNAN LAPORAN KEUANGAN BERBASIS KOMPUTER DI UMKM DAPOER NISWAH - Epi, Yus; Nurlela; natasha, syarifah fadillah; Fadila, Zakia; Yani, Selfitrida A; Siregar, Irma Hariyanti; Maysara, Dinda Putri; Lubis, Dinda Rahmatullah (Cattleya Darmaya Fortuna, 2025)
This community service aims to improve the understanding and skills of the micro business actors at Dapoer Niswah in compiling structured financial reports using Microsoft Excel. The problems faced include unstructured financial records and lack of digital literacy. The method involves training, practice, and mentoring. The results showed significant improvement in knowledge and skills, as well as positive feedback. Excel-based recording is proven effective for practical use in micro businesses.